(untitled) (The Research of Medical Science Review, 2025)
Objective: To study frequency of hypothyroidism and clinical associations in transfusion dependent patients of thalassemia major on chelation therapy Study Design: Analytical cross-sectional study Place and Duration of Study: Pediatrics department of Combined Military Hospital, Sialkot from January 2024 – June 2024 Methodology: A total of 320 patients were included in the final study protocol. Laboratory investigations carried out in all patients included blood complete picture, serum ferritin levels, thyroid profile including thyroid stimulating hormone (TSH) and free T4 levels to determine presence of absence of hypothyroidism and its sub-types. Primary variables studied were frequency of hypothyroidism and its sub-types. Secondary variables included relationship between number of transfusions with severity of thyroid disease Results: Serum ferritin levels between sub-clinical and overt hypothyroidism were less than 2000 mg/ml in 24 (8.0%) versus 00 (0%) patients, between 2000- 3000 mg/ml in 30 (10.0%) versus 00 (0%) patients, between 3000-4000 ng/ml in 186 (61.8%) versus 00 (0%) patients, and more than 4000 ng/ml in 61 (20.3%) versus 19 (100%) patients (p<0.001). Duration of transfusion between both groups showed duration of less than 5 years in 24 (8.0%) versus 00 (0%) patients, 5-10 years in 238 (79.1%) versus 02 (10.5%) patients and more than 10 years in 39 (13.0%) versus 17 (89.5%) patients (p<0.001). Conclusion: Frequency of hypothyroidism sub-type showed sub-clinical hypothyroidism in 301 (79.7%) patients while overt hypothyroidism was found in 19 (5.9%) of patient and are the major sub-type associated with patients on prolonged chelation therapy linked with duration of blood transfusions and levels of ferritin in transfusion dependent thalassemia major pediatric patients.